Mental Health Promotion in School: Schoolchildren’s and Families’ Viewpoint - Kristiina Puolakka; Anne Konu; Irma Kiikkala; Eija Paavilainen (Nursing Research and Practice)
While developing mental health work in schools, it is very important to consider the viewpoint of pupils. Parents can also give remarkable information on their children’s viewpoint. The purpose of this study was to produce a description of the concepts used by schoolchildren aged 12–16 years and their families associated with promoting mental health in schools. The research material comprised interviews with schoolchildren and mothers, and verbal answers from the school well-being profile survey (n=426). The analysis was conducted by applying the grounded theory method as introduced by Strauss. The study was conducted in a Finnish comprehensive school.